Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1253/circj.cj-09-0379
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Matrix Metalloproteinase-1 Plasmid DNA Prevents Left Ventricular Remodeling in Chronic Myocardial Infarction of Rats

Abstract: Background: The present study investigated whether administration of controlled release matrix metalloproteinase-1 (MMP-1) plasmid DNA prevents left ventricular (LV) remodeling in a rat chronic myocardial infarction (MI) model. Methods and Results: Rats with a moderate-sized MI were randomized to 2 groups: injection of phosphate buffered saline (PBS) containing microspheres into the peri-infarct area (MI group, n=14) and injection of cationized gelatin microspheres incorporating MMP-1 plasmid DNA (MI+MMP-1 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…We have confirmed that the profile of the hydrogel degradation and release of nucleic acid is not influenced by the shape and size of hydrogel [99]. So far, the controlled release system of nucleic acids with the cationized gelatin hydrogels has succeeded in the regeneration therapies for fibrosis [73], [100], [101], [102], [103], aortic aneurysms [104], and autoimmune alopecia [105].…”
Section: Regenerative Therapy Based On Nucleic Acids Of Ddssupporting
confidence: 68%
“…We have confirmed that the profile of the hydrogel degradation and release of nucleic acid is not influenced by the shape and size of hydrogel [99]. So far, the controlled release system of nucleic acids with the cationized gelatin hydrogels has succeeded in the regeneration therapies for fibrosis [73], [100], [101], [102], [103], aortic aneurysms [104], and autoimmune alopecia [105].…”
Section: Regenerative Therapy Based On Nucleic Acids Of Ddssupporting
confidence: 68%
“…Infarct size was determined by 2,3-,5-triphenyltetrazolium chloride (TTC) staining, and was expressed as ratio of the surface area of the infarct wall to the entire surface area of the LV (Vandegriff et al, 2008). The heart section was also stained with Masson's trichrome to assess fibrosis as previously described (Lin et al, 2009;Yeh et al, 2010). The infarct area was visible as white and non-infarct as red after being stained with TTC.…”
Section: Determination Of Infarct Size and Histologymentioning
confidence: 99%
“…Another potential target for finely tuned delivery post-MI is MMPs. Lin et al delivered MMP-1 plasmid DNA in microparticles to reduced scarring post-MI 28 . However, MMPs have another important role in contributing to post-MI damage that was not targeted in the Lin et al study, namely breakdown of native extracellular matrix (ECM) proteins immediately following ischemic injury and cardiomyocyte death 92 .…”
Section: Discussionmentioning
confidence: 99%